Implementasi Program Makan Bergizi Gratis (MBG) Melalui Kolaborasi Akademisi Universitas Terbuka Di Yayasan Pondok Pesantren Al-Kautsar, Tangerang Selatan - Elpipres Niku; Mudayat Mudayat; Imam Syafei’i; Eko Yuliastuti Endah Sulistyawati; Ichwan Ichwan; Andayani Andayani; Siti Julaeha; Ikhsan Ikhsan (Yayasan Darussalam Bengkulu, 2026)
The Free Nutritious Meals Program (MBG) is a 2026 national strategic policy aimed at improving the quality of Indonesian Human Resources (HR) from an early age. Universitas Terbuka (UT) carried out Community Service (PkM) activities at the Al-Kautsar Islamic Boarding School Foundation in Pamulang, South Tangerang, with the aim of accompanying the implementation of the program scientifically and structurally. The main problems faced were the lack of understanding among the school kitchen managers regarding the diversification of balanced nutritious menus, hygiene standardization, and food management based on local ingredients. The implementation method comprises four stages: field observation, education through the “Isi Piringku” workshop, action accompaniment in menu preparation, and regular monitoring. The results showed an 88.9% increase in nutritional literacy of managers based on pre-test and post-test results, the formation of nutritionally standardized weekly menus, and significant improvement of kitchen sanitation systems. This collaboration proves that universities can be effective catalysts in the success of government programs in religious-based educational institutions, while contributing to improving the nutritional status and learning achievement of students.